Photochemical and photocatalytic degradation of 1‐propanol using UV/H2O2: Identification of malonate as byproduct. Issue 18 (6th March 2019) - Ferreira Santos, Mauro Sergio; Gomes Cordeiro, Thiago; Cieslarova, Zuzana; Gutz, Ivano Gebhardt Rolf; Garcia, Carlos D.
Abstract: 1‐propanol is a primary alcohol extensively used in the pharmaceutical, chemical, and food industries. It has been also found as a contaminant in the atmosphere and is considered a model compound to mimic the behavior and fate of aliphatic alcohols exposed to environmental conditions. In order to understand that role of relevant variables, this paper presents results obtained with a simple experimental set‐up to investigate the reactivity of 1‐propanol under mild oxidizing conditions. Coupling this system with CE‐C 4 D allowed the quantification of the carboxylic acids formed. For the described experiments, aqueous solutions of 1‐propanol were placed inside a photoreactor and oxidized upon the addition of TiO2 and/or H2 O2 . According to the described results, the addition of H2 O2 (0.1% w/w) was the most significant variable, roughly tripled the amount of carboxylic acids generated and led to the conversion of up to 70% of the initially available 1‐propanol (1 mmol/L). More importantly, the reaction yielded the formation (within 10 min) of propionate (50 µmol/L), acetate (400 µmol/L), formate (50 µmol/L), and malonate (200 µmol/L). The latter is critically important because it represents the first example of the photochemical oxidation of both terminal carbons of the C3 ‐chain of 1‐propanol under mild conditions, and opens new avenues for the production of this important chemical building block.